2009
DOI: 10.1371/journal.pone.0006964
|View full text |Cite
|
Sign up to set email alerts
|

Something Old, Something New, Something Borrowed; How the Thermoacidophilic Archaeon Sulfolobus solfataricus Responds to Oxidative Stress

Abstract: To avoid molecular damage of biomolecules due to oxidation, all cells have evolved constitutive and responsive systems to mitigate and repair chemical modifications. Archaea have adapted to some of the most extreme environments known to support life, including highly oxidizing conditions. However, in comparison to bacteria and eukaryotes, relatively little is known about the biology and biochemistry of archaea in response to changing conditions and repair of oxidative damage. In this study transcriptome, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 100 publications
(117 reference statements)
3
73
0
Order By: Relevance
“…Relative expression data show similar transcript levels of SOD (Equation 7) and internal PRX (Equation 8) in both organisms at all sites, which may indicate co-expression of these two genes to coordinate the removal of ROS inside the cell, as previously observed in the archaeon Sulfolobus solfataricus where they form an enzymatic complex (Maaty et al, 2009). Normalized expression of these two genes is higher in M. yellowstonensis than in Hydrogenobaculum in BE_d, ECH_b, and ECH_c Fe(III)-oxide mats, which may reflect a higher level of internal oxidative stress in the bacterial population, and thus a higher cellular response to mitigate ROS.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Relative expression data show similar transcript levels of SOD (Equation 7) and internal PRX (Equation 8) in both organisms at all sites, which may indicate co-expression of these two genes to coordinate the removal of ROS inside the cell, as previously observed in the archaeon Sulfolobus solfataricus where they form an enzymatic complex (Maaty et al, 2009). Normalized expression of these two genes is higher in M. yellowstonensis than in Hydrogenobaculum in BE_d, ECH_b, and ECH_c Fe(III)-oxide mats, which may reflect a higher level of internal oxidative stress in the bacterial population, and thus a higher cellular response to mitigate ROS.…”
Section: Discussionsupporting
confidence: 71%
“…Normalized expression of these two genes is higher in M. yellowstonensis than in Hydrogenobaculum in BE_d, ECH_b, and ECH_c Fe(III)-oxide mats, which may reflect a higher level of internal oxidative stress in the bacterial population, and thus a higher cellular response to mitigate ROS. Higher FDX gene transcripts detected in Hydrogenobaculum at all sites also support this hypothesis, as ferredoxin is involved in maintaining intracellular redox potentials (Maaty et al, 2009). In Hydrogenobaculum spp., both rubrerythrin (11) and ferredoxin (Equation 12) enzymes (Weinberg et al, 2004) may participate equally in Fe cycling, as indicated by comparable expression levels at all sites.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations